GLP-1 Receptor Agonists: A New Hope in the Global Fight Against Obesity — Benefits and Health Risks - Pastuszek, Oskar; Borowski, Konrad; Radziwon, Maja; Bolesta-Okuniewska, Emilia; Michalak, Paweł; Marchwińska-Pancer, Aleksandra; Kopeć, Katarzyna; Ceryn, Julia; Wicher, Anna (Journal of Education, Health and Sport, 2026)
Introduction. Global obesity has reached unprecedented levels, with approximately one billion people worldwide suffering from obesity. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have proven to be highly effective agents for weight management, resulting in significant weight loss and improvements in metabolic, cardiovascular, and renal outcomes. Nevertheless, serious concerns remain regarding long-term safety, including gallbladder disease, rare gastrointestinal complications, potential risk of pancreatitis, concerns related to perioperative aspiration, psychiatric symptoms, and significant weight regain after discontinuation of the drug. Research objective. This review synthesizes the current evidence on the benefits and risks of GLP-1 RA use, highlighting implications for clinical practice, long-term therapy, and future research priorities. Methodology. This review is based on a structured search of the PubMed database up to November 2025. Keywords included “GLP-1 receptor agonist,” “semaglutide,” “liraglutide,” “tirzepatide,” “obesity,” “weight loss,” “pancreatitis,” “gallbladder,” “body composition,” and “safety.” Priority was given to randomized controlled trials, meta-analyses, large observational studies, and WHO technical documents on the pharmacotherapy of obesity. Articles were analyzed for their relevance to efficacy, safety, or body composition outcomes. Conclusions. GLP-1 inhibitors represent a major advance in obesity treatment, offering robust weight loss and metabolic benefits, but their use requires careful management of side effects and long-term risks. Ongoing research is needed to optimize therapy, address safety concerns, and ensure equitable access.